The Appraisal of Conductions - Bermejo-Luque, Lilian (Informal Logic, 2019)
I argue that conductions are a special type of inference indeed, but that this does not mean that we need to develop novel standards of inference goodness or specific argument schemes for properly assessing them. Following LNMA’s theoretical framework, I provide a semantic account of conductions and explain the interesting pragmatic properties of a certain type of conductions (i.e., balance of considerations or pro-and-con argumentation) in terms of the rhetorical dimension of the speech-act of arguing.